PENGARUH PEMANFAATAN MEDIA EDMODO DAN KREATIVITAS TERHADAP HASIL BELAJAR BAHASA INGGRIS - Mulyadi NA; Priyo Susilo (Akademika : Jurnal Teknologi Pendidikan, 2017)
This study aims to prove that: 1) differences in English learning result he teacheswith the utilization of Edmodo media with students taught by print media. 2) the presence ofEdmodo media usage and creativity. 3) Differences in english learning outcomes of studentswho taught using Edmodo media and taught by print media ifor students who have highcraternity. 4) differences in English learning outcomes of students taught using Edmodomedia and students taught by print media for students who have low creativity. In thisexperiment we use experimental method using 2X2 factorial group design. The target of thisresearch is all officer students of police language school. The member of population consistsof 140 students each class consisting of 20 students. Based on the results of hypothesis testingand discussion, it is concluded that the learning outcomes of students using Edmodo mediaare better than the students who use print media, secondly, the existence of learning mediausage intraction and creativity toward English learning result. Third students who useEdmodo media have hight creativity than students who use print media. Fourth, studentswho use print media creativity is lower than the students using Edmodo media.